Boosting water oxidation electrocatalysts with surface engineered amorphous cobalt hydroxide nanoflakes. Issue 27 (4th July 2018) - Zhang, Haoxuan; Chen, Bingxu; Jiang, Hao; Duan, Xuezhi; Zhu, Yihua; Li, Chunzhong
Abstract : The sulfur engineering of cobalt hydroxide can produce more targeted active intermediates, hence maximizing the OER performance in alkaline media. Abstract : Enriching dominant active intermediates is most pivotal in developing efficient non-noble oxygen evolution reaction (OER) electrocatalysts for water oxidation. Herein, we report surface-engineered amorphous cobalt hydroxide nanoflakes on nickel foam as highly active electrocatalysts for boosting water oxidation by a new repeatedly switching current–polarity strategy. It is discovered that sulfur introduction can simultaneously increase the Co 3+ /Co 2+ ratio to generate more targeted OOH* intermediates and regulate the surface electronic structure to greatly boost its intrinsic activity. The density functional theory (DFT) calculations further confirm the reduction of the free energy of the OOH* intermediates. Consequently, our Co(OH) x S electrocatalyst exhibits an ultralow overpotential of 283 and 365 mV at 100 and 1000 mA cm −2 in alkaline media, respectively, and its turnover frequency (TOF) is more than 4 times higher than the corresponding Co(OH) x catalysts. This heteroatom triggered surface engineering may open up avenues to explore other efficient non-noble metal electrocatalysts for water oxidation.